Made in Canada : craft and design in the sixties (Published for Design Exchange, Toronto in collaboration with the Canadian Museum of Civilization by McGill-Queen's University Press, 2005)
""Contents""; ""Preface""; ""Foreword: Design Exchange""; ""Foreword: Canadian Museum of Civilization""; ""Introduction: Canada in the Sixties â€? ""It can do almost anything""""; ""DESIGNING A MODERN NATION""; ""1. When ""la Dolce Vita"" Met ""True Canadianism"" Canadian Airports in the Sixties""; ""2.""Instant World"" Canada and Space-Age Design in the Sixties""; ""3.A Flag for Canada""; ""CANADA WELCOMES THE WORLD""; ""4. Excellence, Inventiveness, and Variety Canadian Fine Crafts at Expo 67""; ""5. Habitat ' 67 View from the Inside""; ""SAME DECADE, DIFFERENT STYLES""